Threats to Coping: The Combined Effects of Vicarious Trauma and Alarm Fatigue on Health Care Professionals - Mona Khurshid; Dr. Rubina Hanif (Research Journal of Psychology, 2025)
Aim This study examines the connection between vicarious trauma, alarm fatigue, and coping self-efficacy in healthcare workers. It aims to explore how these stressors impact healthcare workers' psychological resilience and capacity to manage workplace demands. Method A quantitative research methodology was employed, utilizing a structured questionnaire distributed to a sample of 200 healthcare workers. The questionnaire assessed levels of vicarious trauma, alarm fatigue, and coping self-efficacy. Results The findings revealed a strong negative correlation between vicarious trauma and coping self-efficacy. Additionally, alarm fatigue was shown to exacerbate this negative relationship. Specifically, healthcare workers experiencing higher levels of both alarm fatigue and vicarious trauma reported significantly lower coping self-efficacy. Conclusion These results are consistent with previous research highlighting the risks of burnout, compassion fatigue, and decreased job performance among healthcare professionals. The study emphasizes the urgent need for targeted interventions to mitigate the effects of vicarious trauma and alarm fatigue and to enhance healthcare workers' coping abilities.